TEXTBOOK WRITING WORKSHOP: STRATEGIES AND CHALLENGES IN COMPILING QUALITY TEXTBOOKS - Ramadhanti, Dina (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
Writing textbooks needs to be done by lecturers to improve the quality of teaching in the classroom. Lecturers can compile textbooks according to student learning needs and according to the learning plan that has been prepared together with the team of lecturers teaching the course. In the context of compiling the textbooks, lecturers still experience obstacles including the completeness of the structure and suitability with the learning plan, reference sources that are still not up to date, textbooks that are not market-oriented, and not oriented to the latest developments in science and technology. After the material delivery session was carried out, it was continued with a question and answer session. From the material delivery session, a strategy for writing textbooks was obtained, namely starting from planning, compiling chapters per chapter/unit, and evaluation/review. Based on the questions and answers conducted with participants, information was obtained about the challenges in writing textbooks. The challenges faced are related to the number of pages of textbooks, plagiarism checks in writing textbooks, revision of textbooks, preparation of textbooks based on RPS, suitability of courses with research and community service carried out, costs of publishing books, factors in writing textbooks, writing textbook titles, lecturers in writing textbooks, criteria for textbooks that are in accordance with market tastes, ways for local textbooks to become national books, the potential for translated books to become textbooks, and how to present textbooks using formulas for exact courses.